Community Service Activities - Counseling And Blood Pressure Screening (Hypertension Disease) - Ernawati Ernawati; Alexander Halim Santoso; Sukmawati Tansil Tan; Yohanes Firmansyah; Anggita Tamaro; William Gilbert Satyanegara (Jurnal Pengabdian Masyarakat, 2023)
High blood pressure, also known as hypertension, is a severe health issue that has a significant impact on the quality of life of individuals. The purpose of community service activities that emphasize counseling and screening for high blood pressure is to raise public awareness of the significance of maintaining normal blood pressure and detecting and preventing hypertension early. Through this community service project, it is anticipated that greater awareness will be generated regarding the significance of maintaining normal blood pressure and preventing hypertension. People are becoming more committed to adopting a healthy lifestyle and undergoing routine blood pressure tests. The result will be a decrease in the incidence of hypertension, an improvement in life quality, and a decrease in the severity of complications associated with high blood pressure. Counseling and screening for high blood pressure are concrete measures in efforts to prevent and control diseases that pose a threat to public health. Through this strategy, it is anticipated that individuals will be more aware of the significance of cardiovascular health and have the necessary knowledge and skills to maintain normal blood pressure.